Typical Errors in the Writing of the Students Participating in Mawapres Selection in ITS Surabaya (NOBEL: Journal of Literature and Language Teaching, 2015)
One of the elements in the selection of the â€œITS Heroes 2015â€ to be the candidates for National Selection for Student Competition (Mawapres) is the ability of the participants to communicate in English in the form of writing and speaking performance. In the writing performance, the participants must submit an English abstract of their papers, and in the speaking performance, the participants are required to tell themselves in English. From these two evaluation items, the abstract is more interesting to analyze in terms of the writing errors the participants made in it. This paper presents the analysis of the common writing errors made by the participants of â€œITS Heroes 2015â€. The errors are categorized and analyzed based on the checklist items by adopting Kim (2009)â€™s error classification system, which is based on Dulay, Burt, and Krashenâ€™s classification system.